Ďábel v zeleném: Ekologické a environmentální rysy českých satanistů - Jahl, Jakub (Lidé města, 2022)
This article deals with the ecological and environmental tendencies of the two largest Satanic groups in the Czech Republic. It first recapitulates the connection between mainstream religions and ecology. It then describes the absence of Satanism in major scholarly publications and uncovers a strong link between Satanism and ecology/animal rights. The text illustrates this in the words of Anton LaVey, Peter H. Gilmore, and several Satanic organizations including the Church of Satan, Temple of Set, Dragon Rouge, The Satanic Temple, and others. The article concludes by looking for ecological tendencies in the teachings of the two largest Satanic groups in the Czech Republic – the local version of LaVey’s Church of Satan and the Czech-influenced Community of Satan. Finally, the text briefly mentions the main research findings of these groups and concludes by showing them in relation to Bron Taylor’s model of dark green religions.